Analysis of Students' Critical Thinking Skills on Solid Material Elasticity - Surya Haryandi; Misbah Misbah; Mastuang Mastuang; Dewi Dewantara; Saiyidah Mahtari (Kasuari: Physics Education Journal (KPEJ), 2019)
The research aims to analyze students' critical thinking skills (CTS). This type of research is descriptive qualitative. The research subjects consisted of 31 students of Class XI MIPA in one of the high schools in the city of Banjarmasin. The instrument is in the form of 6 CTS test items that measure 2 sub-indicators, namely drawing conclusions from the results of investigating and evaluating (formulating alternative solutions). Descriptive data analysis by describing CTS on the two sub-indicators. The results showed that the CTS of students at this time were still in the low category, which was marked from the percentage of 2 CTS sub-indicators namely drawing conclusions from the results of investigating and evaluating (formulating alternative solutions) which was still low under 10%. Further research needs to be done on CTS which is allegedly capable of being trained through an inquiry model based worksheets.